2013
DOI: 10.1111/jai.12174
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory growth following various time lengths of restricted feeding in rainbow trout (O ncorhynchus mykiss ) under summer conditions

Abstract: SummaryThis study was conducted to determine the effects of various time lengths of restricted feeding at 0.5% of body weight on compensatory growth (CG) in rainbow trout under summer conditions. Seven treatments with triplicate tanks consisted of control (C) fed to satiation over 98 days and the remainder being one (R1) to six (R6) weeks of restriction and then refeeding for the remaining 8 weeks of the experiment. At the end of the experiment R1 and R2 were able to catch up with C. Repeated measures ANOVA su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
(113 reference statements)
1
6
0
Order By: Relevance
“…This decreasing HSI indicates that lipid and glycogen in the liver possibly decrease (used as an energy source) and therefore the protein content in the liver is preserved (Gaylord and Gatlin, ; Peres et al., ). Previous studies reported that HSI values decreased in fish subjected to starvation (Turano et al., ; Eroldoğan et al., ; Peres et al., ; Sevgili et al., ,b). The result for the S3 group showing partial compensation in our study is similar to reports from previous studies.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…This decreasing HSI indicates that lipid and glycogen in the liver possibly decrease (used as an energy source) and therefore the protein content in the liver is preserved (Gaylord and Gatlin, ; Peres et al., ). Previous studies reported that HSI values decreased in fish subjected to starvation (Turano et al., ; Eroldoğan et al., ; Peres et al., ; Sevgili et al., ,b). The result for the S3 group showing partial compensation in our study is similar to reports from previous studies.…”
Section: Discussionmentioning
confidence: 87%
“…(), when a fish requires more energy than it receives from feed it then uses reserve energy for sustenance. A reduction in the amount of body lipid in longer fasting periods occurs and lipid restoration may take time, depending on the fish species (Qian et al., ; Ali et al., ; Sevgili et al., ,b). Therefore, the higher lipid level and a growth rate in the S1 group, despite similar food consumption of the control, may be explained by a shorter food deprivation period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results hint that the key to their survival may be their ability to undertake seasonal energy recovery in spring, compensating for energy loss during winter while building up energetic stores to endure the upcoming summer season (Armstrong and Bond 2013). Many studies on temperate fishes have highlighted the ability to compensate energetic and growth losses during periods of adverse temperatures or food scarcity through increased feeding rate and feeding activity when conditions become favourable again (Sevgili et al 2013; Armstrong and Bond 2013; Furey et al 2016; Peng et al 2017). For P. trichrourus such periods of recovery, where it can access highly nutritious food resources (Shraim et al 2017) under optimal environmental temperatures (Kaschner et al 2016), may be vital for mitigating energy loss during winter and summer, and hence ultimately permit the persistence of abundant populations within the southern Gulf throughout the year.…”
Section: Discussionmentioning
confidence: 99%